Marginalization of Children from Divorced and Unwed Parents: Some Alimony Issues in 1960s Yugoslavia - Vera Gudac Dodić (Токови историје)
The Yugoslav state’s legislative actions throughout the early stages of socialism acknowledged parents’ equality in terms of rights and responsibility to children. This is argued throughout the article by presenting laws that explicitly control parent-child relationships, the status of children from divorced marriages and children born out of wedlock, and difficulties surrounding their maintenance. The paper covers the issues surrounding the legal right to alimony for children of divorced parents and children born out of wedlock in different regions of Yugoslavia across the 1960s.